Gut Microbiota and Host Thermoregulation in Response to Ambient Temperature Fluctuations - Saeid Khakisahneh (American Society for Microbiology, 2020)
ABSTRACT Ambient temperature (Ta) is an important factor in shaping phenotypic plasticity. Plasticity is generally beneficial for animals in adapting to their environments. Gut microbiota are crucial in regulating host physiological and behavioral processes. However, whether the gut microbiota play a role in regulating host phenotypic plasticity under the conditions of repeated fluctuations in environmental factors has rarely been examined. We used intermittent Ta acclimations to test the hypothesis that the plasticity of gut microbiota confers on the host a metabolic adaptation to Ta fluctuations. Mongolian gerbils (Meriones unguiculatus) were acclimated to intermittent 5°C to 23°C, 37°C to 23°C or 23°C to 23°C conditions for 3 cycles (totally 3 months). Intermittent Ta acclimations induced variations in resting metabolic rate (RMR), serum thyroid hormones, and core body temperature (Tb). We further identified that the β-diversity of the microbial community varied with Ta and showed diverse responses during the 3 cycles. Some specific bacteria were more sensitive to Ta and were associated with host dynamic metabolic plasticity during Ta acclimations. In addition, depletion of gut microbiota in antibiotic-treated gerbils impaired metabolic plasticity, particularly at low Ta, whereas supplementation with propionate as an energy resource improved the inhibited thermogenic capacity and increased the survival rate in the cold. These findings demonstrate that both gut microbiota and their host were more adaptive after repeated acclimations, and dynamic gut microbiota and their metabolites may confer host plasticity in thermoregulation in response to Ta fluctuations. It also implies that low Ta is a crucial cue in driving symbiosis between mammals and their gut microbiota during evolution. IMPORTANCE Whether gut microbiota play a role in regulating host phenotypic plasticity in small mammals living in seasonal environments has rarely been examined. The present study, through an intermittent temperature acclimation model, indicates that both gut microbiota and their host were more adaptive after repeated acclimations. It also demonstrates that dynamic gut microbiota confer host plasticity in thermoregulation in response to intermittent temperature fluctuations. Furthermore, low temperature seems to be a crucial cue in driving the symbiosis between mammals and their gut microbiota during evolution.